The Coronavirus Crisis as Catalyst for EU Legitimacy? Italian Public Opinion and the EU during the Pandemic - Basile, Linda; Cilento, Marco; Conti, Nicolò (PARTECIPAZIONE E CONFLITTO, 2021)
Over the past few years, the EU has been challenged by multiple disintegration forces sustained by a growing number of Eurosceptic citizens. In this critical scenario, Italy has emerged as a relevant case because of its transformation from a leading pro-integration country to a country where EU integration is an increasingly divisive issue. We explore the relationship between Italian public opinion and the EU, with a specific interest in understanding how the coronavirus crisis may affect such a relationship, supposing that our case study may also be revealing as to how a crisis context can produce eﬀects on the popular legitimacy of the EU. We show that in Italy there is demand from some majoritarian segments of society for stronger cooperation in the EU. To explain the apparent paradox of why Italians decreasingly feel that their country beneﬁts from the EU but still want to increase EU cooperation in certain areas, we turn to the argument of the public's instrumental approach to the principle of burden-sharing: citizens support deeper integration to face the costs of the most pressing crises aﬀecting the country and the EU at large.